A real-world analysis of 1,823 hospitalized osteoporotic fractures in Northeast China - Meng, Qi; Wang, Xinwei; Gao, Yuzhong; Leslie, William D.; Lix, Lisa M.; Shi, Xianbao; Kan, Bo; Yang, Shuman (Frontiers in Endocrinology, 2025)
ContextThere are limited real-world data evidence assessing the clinical characteristics of hospitalized osteoporotic fractures in China.ObjectiveTo investigate the clinical characteristics of hospitalized major osteoporotic fractures in Northeast China.MethodsWe identified hospitalized fracture patients aged 50 and over from the First Affiliated Hospital of Jinzhou Medical University between January 1, 2018, and December 31, 2022. Major osteoporotic fractures including hip, vertebral, forearm and wrist, and humerus were diagnosed based on x-ray reports extracted from the electronic medical records (EMR). The cause of fracture, comorbidities, surgical methods, and anti-osteoporotic medications (AM) use were extracted from EMR.ResultsThe study population included 1823 fracture patients, 510 males and 1313 females. Over half of fracture patients were aged over 70 years. Hip fractures accounted for 68.4% of all fractures in males and 57.9% in females. For those with hip fractures, the most common sites were the femoral neck (62.9%) and intertrochanteric (35.3%). Most fractures were due to falls (81.0% in males and 80.2% in females). The two most common comorbidities for males and females were hyperlipemia (45.9% vs. 47.1%) and hypertension (38.2% vs. 41.6%). Only 4.7% males and 8.6% females were treated with AM.ConclusionsHip fractures, especially femoral neck fractures, accounted for the majority of osteoporotic fractures in a tertiary public hospital in Northeast China. Common comorbidities in these fracture patients were hyperlipemia and hypertension. There was a very low rate of AM use among these patients.